Comics as an assessment tool for learning Mathematics - Liberty Gay Manalo (Universidade Estadual de Alagoas, 2024)
This research investigates the perceptions of 2nd-year pre-service mathematics teachers regarding the utilization of comics as an assessment tool for Linear Algebra. Employing an exploratory descriptive design and employing a semi-structured interview questionnaire, the thematic analysis revealed noteworthy themes. These include the effectiveness of comics in enhancing conceptual understanding, their practical application and integration into mathematical concepts, their role in classroom utilization and knowledge sharing, their contribution to the development of creativity, critical thinking, and research interest among teachers. The study also highlights themes regarding comics' role in fostering learning and reflection, facilitating discovery, and improving learning outcomes as well as knowledge sharing and student sense of ownership. This study concludes that comics have promising potential as an assessment tool and suggests more research to improve ways for best integration in classrooms.